MOTIVATION AND BEHAVIOR OF OLDER PEOPLE ASSIST SEGMENTING THE MATURE MARKET ANDIDENTIFYING SENIOR TOURISTS' EXPECTATION - Rahmawati, putu indah (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2011)
The implication of the growing number of mature people is becoming contemporary issues for tourism and hospitality business. Managers need to have better understanding about the motives of older people to go travelling and how they behave in the tourist destination, what their need and expectation are. This report attempts to extend the theoretical and empirical evidence about the relationship among older people motivations, behaviours, expectations and mature market segmentation. The .findings of literature reviews also reveal the differences of senior traveller motivation and expectation due to differences of nationality and culture background. Finally, this study highlighted the implication of this issue to the tourism and hospitality businesses.